(untitled) (Eurasian Medical Research Periodical, 2025)
Chronic Generalized periodontitis is one of the most common inflammatory and destructive pathologies of periodontal tissues and is a leading cause of premature tooth loss in adults. The disease is characterized by a multifactorial etiology, complex pathogenesis, and a close relationship with general somatic pathology. This article presents an analysis of current data on the etiological factors and pathogenetic mechanisms of the development of chronic generalized periodontitis. The clinical manifestations of the disease depending on the severity, modern diagnostic methods, including clinical, radiological, and laboratory approaches are considered. Particular attention is paid to the principles of comprehensive treatment, including conservative, surgical, and preventive measures aimed at stabilizing the pathological process and preventing relapse. The need for an individualized and interdisciplinary approach to the management of patients with chronic periodontitis is demonstrated. generalized periodontitis.